EVALUASI PERHITUNGAN HARGA POKOK PRODUKSI DALAM PENCAPAIAN LABA PADA MEBEL ANGEL PROFIL - Marpaung, Christine Marpaung Sada M; Liawan, Calvin; Sidik, Gregorius Thomas (Jurnal Pitis AKP, 2021)
The goal of this study is to learn how to calculate the cost of production to achieve profit on the Angel Furniture Profile based on the issues that will be covered in the study. This study focused on the manufacturer of doors, cabinets, windows, and tables, Angel Profil Furniture. This research is a quantitative descriptive study whose data was acquired using an interviewing strategy, then evaluated using a descriptive analysis technique and quantitative approach. The method employed in this study uses a full costing methodology to compute the cost of production and is in the form of cost data that includes the costs of labor, raw materials, and factory overhead. Full costing can assist business owners in determining their profit.